Effect of Psychological Distress on Mental Well-Being among Adolescent Students - S, Sharanya.; Kumara V, Hemantha (Journal of Neonatal Surgery, 2025)
The stage of Adolescents is considered be the most crucial and important stages of physical and emotional development among the various stages of development. Adolescents in the recent times have their struggle to manage stress and distress, there by largely affecting their mental well-being. This not affects their immediate skill set but also creates a lag in their growth towards the next stages of life. The present study focused on studying the effect of Psychological Distress on Mental Well-being among Adolescent students. A total sample of 191 students sample was obtained after using standardised screening tests by Depression Anxiety Stress scale – twenty one item ( short version) and ( WEBMBS) Warwick Edinburgh Mental Well-being Scale, students who scored mild-moderate on psychological well-being and medium-low on mental well-being were screened. The results were analysed using the test of significance and Pearson product moment method. In this study it was hypothesized that Psychological distress will have no impact on Mental well-being. In conclusion, Psychological distress has negative impact on Mental Well-being.